2017
DOI: 10.1038/s41598-017-08921-y
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord extracts improve diabetic abnormalities in bone marrow-derived mesenchymal stem cells and increase their therapeutic effects on diabetic nephropathy

Abstract: Bone marrow-derived mesenchymal stem cells (BM-MSC) has been applied as the most valuable source of autologous cell transplantation for various diseases including diabetic complications. However, hyperglycemia may cause abnormalities in intrinsic BM-MSC which might lose sufficient therapeutic effects in diabetic patients. We demonstrated the functional abnormalities in BM-MSC derived from both type 1 and type 2 diabetes models in vitro, which resulted in loss of therapeutic effects in vivo in diabetic nephropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 43 publications
1
46
0
1
Order By: Relevance
“…Human umbilical cord can be mixed, filtrated or pelleted, the extract increases the in vitro proliferation and migration of fibroblasts, as described in the literature (Van Pham et al, 2014;Bakhtyar et al, 2017;Nagaishi et al, 2017;Saito et al, 2018). Original data from our laboratory have shown that increasing protein concentrations of HUC extract enhance fibroblast proliferation (after 48 h) and migration (16 h) (Figure 2).…”
Section: Huc Byproduct: Extractsmentioning
confidence: 84%
“…Human umbilical cord can be mixed, filtrated or pelleted, the extract increases the in vitro proliferation and migration of fibroblasts, as described in the literature (Van Pham et al, 2014;Bakhtyar et al, 2017;Nagaishi et al, 2017;Saito et al, 2018). Original data from our laboratory have shown that increasing protein concentrations of HUC extract enhance fibroblast proliferation (after 48 h) and migration (16 h) (Figure 2).…”
Section: Huc Byproduct: Extractsmentioning
confidence: 84%
“…The treatment based on MSCs from DM mice could not alleviate the kidney damage in DM mice, which might result from abnormal endogenous bone marrow MSCs caused by the high glucose (HG). Monitoring MSCs subsets in the peripheral blood was suggested to predict the diabetic progression and the effectiveness of the therapy [25,37]. Many studies were conducted to gure out the mechanism of MSCs therapy, and one caveat is that a slight move in one part may affect the situation as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…hUCB-MSCs conditional medium (CM) inhibited NRK-52E EMT induced by TGF-β1 in a concentration-dependent manner [14]. As mentioned before, the dysfunction of stem cells was observed in DM patients, but WJs, a mixture of growth factors, extracellular matrix and exosomes extracted from human umbilical cord, could improve BM-MSCs abnormality in proliferation, cell motility, endoplasmic reticulum, mitochondria degeneration, endoplasmic reticulum function and exosomes secretion [25]. ADSCs-CM decreased the expression of caspase-3, ameliorated podocytes apoptosis in a dose-dependent way and maintained the normal podocytes morphology.…”
Section: Secretion Of Tropic Factorsmentioning
confidence: 93%
See 1 more Smart Citation
“…The relative mRNA expression of Igf-1 was downregulated, whereas Ifn-γ, Il-1β , Il-2, and Rantes were up-regulated in treated rats as compared to controls. The expressions of α-Sma, which represented the stress fiber of MSCs, was also increased 11 .…”
Section: Mesenchymal Stem Cells For Diabetic Nephropathymentioning
confidence: 94%